Peran Kegiatan Pramuka dalam Penanaman Pendidikan Karakter Siswa SD Negeri 2 Barenglor - Rofiana Prilia Anisa; Diah Ayu Sekar Ningrum; Nela Rofisian (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The purpose of this research is to describe, 1) the process of scouting activities at Sd N 1 Bareng Lor 2) the suitability of scouting activities with the agreed MoU 3) the students' sense of responsibility in obeying activity regulations. This research uses a qualitative approach, descriptive analysis method, namely research where data collection is carried out in the field. The results of this research will discuss 1) The process of scouting activities at Sd N 1 Bareng Lor, training is carried out to shape students to have skills in knowledge, skills and responsibilities regarding the world of scouting, the material taught is not only about theories but also the application of theory through practice. 2) Conformity of Scouting Activities with the agreed MoU 3) Students' sense of responsibility in obeying activity regulations is very necessary in scouting activities, because when students already have a sense of responsibility within themselves to take part in scouting activities automatically students can also obey the rules in the activity scout well.